2010
DOI: 10.1007/s13277-010-0125-6
|View full text |Cite
|
Sign up to set email alerts
|

Papillary thyroid carcinoma shows elevated levels of 2-hydroxyglutarate

Abstract: Elevated levels of D: -2-hydroxyglutarate (D: -2-HG) occur in gliomas and myeloid leukemias associated with mutations of IDH1 and IDH2. L: -2-Hydroxyglutaric aciduria, an inherited metabolic disorder, predisposes to brain tumors. Therefore, we asked whether sporadic cancers, without IDH1 or IDH2 hot-spot mutations, show elevated 2-hydroxyglutarate levels. We retrieved 15 pairs of frozen papillary thyroid carcinoma (PTC) and adjacent non-neoplastic thyroid, and 14 pairs of hyperplastic nodule (HN) and adjacent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…IDH mutations can be detected by different methods including polymerase chain reaction (PCR)-based assays [20,[55][56][57], expression of IDH1 mutant protein in the tumor tissue by immunohistochemistry [58,59], and detection of the putative oncometabolite, D-2HG, by gas chromatography/ mass spectrometry in vitro or by magnetic resonance spectroscopy in vivo [8,60,61].…”
Section: Methods Of Detecting Idh Mutations and Oncometabolite D-2hgmentioning
confidence: 99%
“…IDH mutations can be detected by different methods including polymerase chain reaction (PCR)-based assays [20,[55][56][57], expression of IDH1 mutant protein in the tumor tissue by immunohistochemistry [58,59], and detection of the putative oncometabolite, D-2HG, by gas chromatography/ mass spectrometry in vitro or by magnetic resonance spectroscopy in vivo [8,60,61].…”
Section: Methods Of Detecting Idh Mutations and Oncometabolite D-2hgmentioning
confidence: 99%
“…Although the source of 2-HG is not fully understood, experimental evidences indicate that IDH1 and IDH2 have a role in the production of d-2-HG (Matsunaga et al, 2012). d-2-HG and its enantiomer l-2-HG are linked to the Krebs cycle (Raimundo et al, 2011) and are found to be elevated in certain types of cancer (Dang et al, 2009;Rakheja et al, 2011) and in different variants of the neurometabolic 2-hydroxyglutaric aciduria. In relation to the latter defect, a recent study from Nota et al (2013) reported 12 recessive mutations (Ser193Trp, Arg282Gly, Arg282Cys, Gly167Arg, Pro45Leu, Glu144Gln, Met202Thr, Tyr297Cys, Tyr256*, Ala9Profs*82, A274Ilefs*24, and Arg173Glyfs*2) found in the CIC gene of three individuals and their families that cause combined d-2-and l-2-hydroxyglutaric aciduria.…”
Section: Citrate In Neurodevelopmental Syndromes and Hydroxyglutaric mentioning
confidence: 99%
“…2 Moreover, certain cancer types show elevated levels of 2-HG but contain no mutations in IDH1 or IDH2. 4 It would therefore be interesting to further investigate the role of citrate and SLC25A1 in these cancer types.…”
mentioning
confidence: 99%